The The Role Of Village Government Officials (Village Head) In Addressing Domestic Violence Crimes: Peran Pejabat Pemerintahan Desa (Kepala Desa) dalam Menangani Kejahatan Kekerasan Dalam Rumah Tangga - Sundari, Ariefah; Hayati; Kuncoro, Cipto; Bagus, Shalahuddin Serba (Fakultas Hukum Universitas Tompotika Luwuk Banggai, 2025)
This article examines the role of village government officials, particularly the village head, in addressing Domestic Violence (DV) crimes at the local level. Despite the presence of formal legal mechanisms under Law No. 23 of 2004 on the Elimination of Domestic Violence, cases of domestic abuse continue to increase, including in rural areas such as Ngarum Village, Sekaran District, Lamongan Regency.The purpose of this research is to explore the position of domestic violence as a lex specialis relative to the general provisions of assault under the Indonesian Penal Code, and to identify how village heads contribute to resolving such crimes without always resorting to the judiciary process.This study uses normative legal research with a conceptual and statutory approach. Data were collected from relevant laws and legal doctrines, supported by qualitative analysis of cases in Ngarum Village.The findings of this research show that domestic violence is legally classified as a special criminal offense (lex specialis) distinct from general assault. Moreover, the study reveals that village heads play a strategic role in facilitating early mediation, community reconciliation, and legal awareness to prevent further escalation. This contributes to a deeper understanding of local governance mechanisms in handling sensitive legal issues at the grassroots level.